Mesoscale frontal evolution of the ERICA IOP-5A cyclone - Cameron, Steven R. (Monterey, California. Naval Postgraduate School, 1993)
A synoptic investigation was conducted of the rapid coastal cyclogenesis that occurred during Intensive Observation Period (IOP) 5A of the Experiment on Rapidly Intensifying Cyclones over the Atlantic (ERICA). Navy Operational Regional Analysis and Prediction System (NORAPS) forecasts were examined in order to study the mesoscale frontal evolution associated with this rapidly deepening coastal cyclone. The ability of the NORAPS forecasts to accurately depict the frontal positions and intensity was also investigated. The frontal evolution showed characteristics of a classical occlusion, similar to the Norwegian cyclone model and of marine frontal structure as discussed by Shapiro and Keyser (1990). The frontal evolution was highly influenced by the prior existanse of strong arctic and coastal fronts. These fronts intensified during the course of the storm development and did not develop as a result of the cyclogenesis Approved for public release; distribution is unlimited. Lieutenant Commander, United States Navy http://archive.org/details/mesoscalefrontal1094527129